Família acolhedora: serviço de proteção e cuidado às crianças e adolescentes com direitos violados: a experiência de Belo Horizonte - Valeria Silva Cardoso (2018)
The Foster Family Service is a type of fostering provided by the Special Social Protection of High Complexity in the Social Assistance Policy. This service offers a temporary fostering to children and teenagers who had their rights violated and were separated of their parents. In those cases, the separation is a protection measure until the child or teenager can return to his original family or, if not possible, placed with adoptive parents. The service assures the fostering in a family home, the individualized attention and the living in a community. It allows the development of childrens socialization. In Belo Horizonte, the Foster Family Service exists since nine and nowadays there are twenty-six approved foster families. This study aims to investigate the experience of foster families from Belo Horizonte, during their time fostering, protecting and caring children and teenagers with violated rights. Its a qualitative and exploratory research based on case studies. It used the documentar analysis and semi structured interviews methods. Seven legal guardians from 7 foster families were interviewed. The data was analysed using the Bardins Content Analysis Theory. It delineated the following analysis categories: knowledge about the service; motivation to become a foster family; comprehension about what it means to be a foster family; actions of protection and care during the fostering; the support offered by the professional team of the service; violence and rights violation; attachment x detachment and the final moment of the fostering; thoughts about the childrens original family and the challenges of the process of fostering. Results indicate potentialities and challenges of this type of fostering. It was verified that this Service is not well-known, demanding investments in divulgation campaigns and information about its purpose. The research evidenced the fragility of complementary actions executed by other public policies, specially health and education both indispensable to guarantee the full protection of children and teenagers. Foster families recognize the professional team of the foster service and emphasize the attendance the team provides, including the attendance to the original Family members to reunite them with their children. Its worthy of note that the feeling moving the foster family is the will to help and the concern with those who are living vulnerabilities or risk situations and are in need of protection and care. However, despite of this politically conscious attitude, the majority of foster families dont see themselves as a part of a Social Assistance Policys service - this situation demands bigger efforts in instruction process Keywords: Children and teenagers. Social protection. Integral protection. Foster family. Care.